DEEP LEARNING FOR FACES ON ORPHANAGE CHILDREN FACE DETECTION - Yonky Pernando; Eka Lia Febrianti; Ilwan Syafrinal; Yuni Roza; Ummul Fitri Afifah (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: l -The field of computer vision is research in development technology to obtain information from images and replicate or imitate human visual processes, so that they can understand the objects around them. Deep learning is a term used to describe a new era in learning that supports computer learning from big data machines. Convolutional Neural Networks (CNN) algorithms have made significant progress in the fields of object detection, image classification, and semantic segmentation. ;Object detection is a technique used to identify the type of object in a given image and the location of the object in the image. The field of computer vision is research in development technology to obtain information from images and replicate or imitate human visual processes, so that computers can know objects around them. Deep learning is the buzzword as a new era in machine learning that trains computers to find patterns from large amounts of data. Convolutional Neural Networks (CNN) algorithms have made significant progress in the fields of object detection, image classification, and semantic segmentation. Object detection is a technique used to identify the type of object in a particular image as well as the location of the object in the image. Keywords: CNN, Computer Vision, Deep Learning, Face Detection;  Abstrak: 1 Bidang computer vision merupakan penelitian dalam teknologi pembangunan untuk memperoleh informasi dari citra dan mereplikasi atau meniru proses visual manusia, sehingga dapat memahami objek - objek disekelilingnya. Pembelajaran mendalam adalah istilah yang digunakan untuk menggambarkan era baru dalam pembelajaran mesin yang memungkinkan komputer belajar dari sejumlah besar data. [Algoritma Convolutional Neural Networks (CNN) telah membuat kemajuan yang signifikan di bidang deteksi objek, klasifikasi gambar, dan segmentasi semantik. Deteksi objek adalah teknik yang digunakan untuk mengidentifikasi jenis objek dalam citra yang diberikan serta lokasi objek di dalam citra. Bidang computer vision merupakan penelitian dalam teknologi pembangunan untuk memperoleh informasi dari citra dan mereplikasi atau meniru proses visual manusia, sehingga komputer dapat mengetahui objek - objek disekelilingnya. Deep learning adalah kata kunci sebagai era baru dalam machine learning yang melatih komputer dalam menemukan pola dari jumlah besar data. Algoritma Convolutional Neural Networks (CNN) telah membuat kemajuan yang signifikan di bidang deteksi objek, klasifikasi gambar, dan segmentasi semantik. /Deteksi objek adalah teknik yang digunakan untuk mengidentifikasi jenis objek dalam citra tertentu serta lokasi objek di dalam citra. Kata kunci: CNN, Computer Vision, Deep Learning, Deteksi Wajah